Quantitative whole body imaging at high field - Cox, Eleanor F (2009)
In this thesis methods of accurately and reproducibly measuring intestinal content and transverse relaxation to study the fate of food in the gastrointestinal tract are reported. In addition to this a technique for measuring relaxation parameters in the brain at ultra-high field is also investigated.